Guidelines for the participation of civil society organizations in OAS activities - (:unkn) unknown (My University, 2016)
The Organization of American States (OAS) has taken a special interest in potentialcontributions by civil society organizations to the activities of its organs, agencies, andentities. For that reason, the OAS Charter assigned the handling of possible specialagreements or arrangements between the Organization and other American agencies ofrecognized international standing to the Permanent Council in 1948. Over the past 50years, the various organs, agencies, and entities of the OAS have developed, in thecontext of their institutional aims, various kinds of relationships with national andinternational institutions.